2003
DOI: 10.1097/01.aud.0000051688.48224.a6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Development of Speech Production Skills in Children Implanted by Age Five

Abstract: Speech production performance in children with cochlear implants is influenced by nonverbal intelligence, gender, implant characteristics including the length of time using the newest speech processing strategies, and educational programs emphasizing oral-aural communication. Factors previously thought to be major contributors to speech production performance, such as age of onset of deafness and age of implantation, did not appear to play significant roles in predicting levels of speech production performance. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
175
3
18

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(207 citation statements)
references
References 33 publications
11
175
3
18
Order By: Relevance
“…However, not all studies showed a negative correlation between the age at implantation and the language outcomes. In a series of comprehensive studies involving 181 prelingually deaf children with cochlear implants, Geers and colleagues failed to find a significant effect of age at implantation on both speech perception and speech production abilities of the children [14][15][16]. Note that a vast majority of the 181 children received cochlear implantation at the ages of 2 -4 years old.…”
mentioning
confidence: 99%
“…However, not all studies showed a negative correlation between the age at implantation and the language outcomes. In a series of comprehensive studies involving 181 prelingually deaf children with cochlear implants, Geers and colleagues failed to find a significant effect of age at implantation on both speech perception and speech production abilities of the children [14][15][16]. Note that a vast majority of the 181 children received cochlear implantation at the ages of 2 -4 years old.…”
mentioning
confidence: 99%
“…This could be inferred from the findings that speech production skills gradually increase with CI experience. Children in this study were achieving articulation proficiencies consistent with much older CI participants with similar amounts of CI experience [6] , and their performance was within 1.5 SD of their normal hearing peers on standardized tests of articulation and receptive vocabulary.…”
Section: Communication Modality Articulation and Vocabulary Skillsmentioning
confidence: 56%
“…Not only in South Africa, but all over the world many areas of healthcare are replete with evidence of socioeconomic status and ethnicity related disparities, with pediatric cochlear implantation being no exception [75][76][77]. The current study population consisted of predominantly Caucasian (62%) children from the private health care system (95%), speaking either Afrikaans (46%) or English (43%).…”
Section: Discussionmentioning
confidence: 99%